2014
DOI: 10.3133/sir20145058
|View full text |Cite
|
Sign up to set email alerts
|

Floods of 2011 in New York

Abstract: For more information on the USGS-the Federal source for science about the Earth, its natural and living resources, natural hazards, and the environment, visit http://www.usgs.gov or call 1-888-ASK-USGS.For an overview of USGS information products, including maps, imagery, and publications, visit http://www.usgs.gov/pubprodTo order this and other USGS information products, visit http://store.usgs.gov Any use of trade, firm, or product names is for descriptive purposes only and does not imply endorsement by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 1 publication
0
17
0
Order By: Relevance
“…Rainfall at Slide Mountain in the headwaters of the Esopus totalled 29.3 cm between 28 and 29 August 2011 during this event (Lumia, Firda & Smith, 2014). The annual exceedance probabilities (AEP) for peak flows at five permanent U.S. Geological Survey (USGS) stream gages in the basin ranged from 0.143 to 0.008 (Lumia et al, 2014), which corresponded to flood recurrence intervals of 7 to >100 years (Table 1). Discharge had nearly receded to pre-flood levels by 7 September 2011, at which point a moderate flood from the remnants of Tropical Storm Lee affected the basin again.…”
Section: Introductionmentioning
confidence: 97%
“…Rainfall at Slide Mountain in the headwaters of the Esopus totalled 29.3 cm between 28 and 29 August 2011 during this event (Lumia, Firda & Smith, 2014). The annual exceedance probabilities (AEP) for peak flows at five permanent U.S. Geological Survey (USGS) stream gages in the basin ranged from 0.143 to 0.008 (Lumia et al, 2014), which corresponded to flood recurrence intervals of 7 to >100 years (Table 1). Discharge had nearly receded to pre-flood levels by 7 September 2011, at which point a moderate flood from the remnants of Tropical Storm Lee affected the basin again.…”
Section: Introductionmentioning
confidence: 97%
“…Synoptic-scale cyclonic systems produce precipitation during all seasons, including Alberta clippers, which originate in the Canadian Rocky Mountains and pick up moisture from the Great Lakes that can then be deposited over our region, and nor'easters, which are coastal storms that can transport moisture from the Gulf of Mexico and the Atlantic Ocean, potentially resulting in intense events during all seasons (e.g., Kocin and Uccellini 1990). During summer, saturated soils are important condition for producing floods (e.g., Lumia et al 2014). In addition, this region experiences warm season convective events are that are associated with warm, humid air masses circulated into this region from the Gulf of Mexico and tropical Atlantic Ocean on the western side of subtropical high-pressure systems.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have found this to be the wettest warm season on record, with more frequent extreme streamflow events (Matonse and Frei, ; Frei et al ., ; Frei and Kelly‐Voicu, ), linked to an increase in the frequency of extreme precipitation events associated with storms of tropical as well as mid‐latitude origin during the warm season (Towey et al ., ). Public perception of the changing regional hydrology during this period, and in particular the extreme events associated with tropical storms Irene and Lee in August and September, 2011 (Lumia et al ., ; Frei and Kelly‐Voicu, ), reflects the uniqueness of this period over the last ~100 years (Solecki et al ., ). In the analysis presented here, whose time domain ends in 2016, it appears as if the pluvial ends in 2012 because the years 2013–2016 were relatively dry.…”
Section: Discussionmentioning
confidence: 97%
“…Regardless of the uniqueness of the recent warm season precipitation record, these and previous results (Matonse and Frei, ; Frei and Kelly‐Voicu, ) suggest that seasonal mean conditions, for both precipitation and streamflow, have been unusually high since the late 1990s; and that the recent increase in seasonal extremes is more pronounced in the streamflow than in the precipitation record. This is consistent with the understanding that the magnitudes of extreme streamflow events are strongly correlated to antecedent conditions as well as to the magnitudes of precipitation events (Lumia et al ., ; Ivancic and Shaw, ; Fang and Pomeroy, ). In other words, during generally wetter conditions, when soils are on average wetter, streamflow will respond more dramatically to warm season precipitation events.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation